A comprehensive policy framework for the development of green markets in European Islands. Issue 1 (31st December 2022) - Kylili, Angeliki; Fokaides, Paris A.; Zachariou, Aravella; Ioannou, Byron; Georgalli, Phoebe-Zoe; Vlachos, Savvas; Skouroupathi, Myrto; Matak, Nikola; Majdandzic, Ljubomir; Olival, Elizabeth; Vasconcelos, Hugo; Cherchi, Vittoria; et al.
ABSTRACT: Under the context of the European Union's energy and environmental strategy toward its decarbonization by 2050, the green markets of the Member States are growing exponentially. The in-place policies and legislation dynamics change substantially in islands and isolated regions due to geographical constraints, limited availability of local resources, economies of scale constraints, and seasonal employment variabilities. This work focuses on assessing policy and legislative elements related to green growth in eight European islands and isolated regions for developing a comprehensive policy scheme. This is achieved by adopting a five-step methodological approach, analyzing the long-term strategies of those regions, and investigating different parameters and dimensions of four sustainability sectors. The outputs of this analysis indicated that although the regions under study are making significant efforts and taking the necessary measures for greening these sectors, they are still behind in fulfilling their EU energy and environmental obligations.